The present status of Bewick’s Swans Cygnus columbianus bewickii in Ukraine - Chovan, Alexander A.; Kazannik, Vitaly V. (Wildfowl, 2015)
A review of the literature on Bewickâ€™s Swans Cygnus columbianus bewickii in UkraineÂ indicated that it was an occasional visitor to the country during the 20th century, withÂ small numbers recorded wintering on the northern coast of the Azov Sea. TheÂ species has occurred more regularly since winter 2006/07, with some tens of birdsÂ counted on the Dnieper River during migration and in the central Syvash on the westÂ coast of the Azov Sea in winter months. Resting and foraging sites were identified onÂ Kiev Reservoir, where numbers of Bewickâ€™s Swans counted peaked at 83 individualsÂ in November 2014. We report here for the first time the importance of the DnieperÂ River in providing staging sites for Bewickâ€™s Swans in Ukraine.